Pengaruh Online Customer Review, Online Customer Rating, Kepercayaan Konsumen, dan Promosi terhadap Keputusan Pembelian Masyarakat Purwokerto Pengguna Tiktok Shop - syafa’at, Faizal; Astuti, Herni Justiana; Hidayah, Arini; Innayah, Maulida Nurul (Universitas Batanghari, 2024)
This study aims to examine the effect of Online Customer Review, Online Customer Rating, consumer trust, and promotion on purchasing decisions at Tiktok Shop in the Purwokerto community. This study applies quantitative methods in order to evaluate the relevance of each variable. The sampling technique using purposive sampling. The instrument for collecting data was a five-level Likert scale questionnaire. The analysis tool uses SPSS. According to the findings of this study, it is known that, consumer confidence has a positive and significant effect on purchasing decisions, promotions have a positive and significant effect on purchasing decisions, while online customer reviews have no positive and insignificant effect on purchasing decisions, online customer ratings have a positive and insignificant effect on purchasing decisions.